Oral intake of rice overexpressing ubiquitin ligase inhibitory pentapeptide prevents atrophy in denervated skeletal muscle - Reiko Nakao (Nature Portfolio, 2021)
Abstract We previously reported that intramuscular injections of ubiquitin ligase CBLB inhibitory pentapeptide (Cblin; Asp-Gly-pTyr-Met-Pro) restored lost muscle mass caused by sciatic denervation. Here, we detected Cblin on the basolateral side of Caco-2 cells after being placed on the apical side, and found that cytochalasin D, a tight junction opener, enhanced Cblin transport. Orally administered Cblin was found in rat plasma, indicating that intact Cblin was absorbed in vitro and in vivo. Furthermore, transgenic Cblin peptide-enriched rice (CbR) prevented the denervation-induced loss of muscle mass and the upregulation of muscle atrophy-related ubiquitin ligases in mice. These findings indicated that CbR could serve as an alternative treatment for muscle atrophy.